Exploring Style : Enhancing the capacity to learn. - Evans, Carol (Education + Training - Volume 50, Edition 2., 2008)
This e-book introduces a selection of papers from the 12th Annual European Learning Styles Information Network Conference on the place of cognitive style in enhancing the capacity to learn. These papers discuss various ways through the cognitive/learning style terminology conundrum to help facilitate advancements in educational practice in a meaningful and informed way. A number of questions are raised regarding the place of cognitive/learning styles in relation to: a broader agenda of learning to learn, state versus trait aspects of styles, along with selected dimensions of powerful learning.